DESAIN GAME EDUKASI ‘ONET WAWASAN NUSANTARA’ (OWA) - Eka Prasetya Adhy Sugara; Mustika Mustika (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
National culture is a precious national heritage, so it must be preserved. The government continues to strive to preserve national culture, the introduction of national culture among students by implementing cultural learning curricula in schools. In addition, the government also holds events such as cultural festivals. However, the efforts made still have weaknesses such as Learning through textbooks is also considered boring and less attractive to students. The cultural festival program is only accessible for the surrounding community so creative solutions are needed as a medium for cultural learning in schools and a means to introduce a culture that can be reached by all people. One of the media that can be used is through games. Games that are currently very easy to play and very familiar in the community are onet games. The purpose of this study was to design the game Onet Wawasan Nusantara (OWA). One method that can be used to design a game is Digital Games Based Learning-Instructional Design (DGBL-ID) which consists of analysis, design, development, quality assurance and implementation stages. The method was chosen because it can integrate the cultural learning curriculum into the game, so that the game not only serves as an entertainment facility, but also has an educational element in it. The results of this study are game design that can be the basis for further game development. In the long run, if this game can be implemented and used by the community (Indonesia), it will be a creative solution that supports government efforts to maintain and preserve national culture.Keywords: edugame, national culture, DGBL-ID